What makes tourists satisfied? an empirical study on Malaysian Islamic tourist destination - Khan, Abdul Highe; Haque, A. K. M. Ahasanul; Rahman, Muhammad Sabbir (IDOSI Publications, 2013)
The main objective of this study is to explore influencial factors that lead to tourist’s satisfaction in destination based Islamic tourist destinations in Malaysia. This research is necessary to provide a better understanding of the Muslim tourist satisfaction in Malaysian Islamic tourist destination in the different facets. The identification of influencing factors that make Muslim tourist satisfied help Islamic destination marketer to make strategic marketing plans. Multiple Regressions was employed to identify the relationship among the variables. From the analysis it was found that destination image, religious motivation and service quality have a positive relationship with tourist satisfaction on islamic tourist destination in Malaysia